PKM Pengembangan Sistem Informasi Akuntansi Untuk Usaha Kecil Dan Menengah (UKM) - Nining Rahaningsih; Fathurrohman; Mulyawan; Maria Dewanty Rafu; Hari Sutrisno (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Small and Medium Enterprises (SMEs) play a crucial role in the national economy, yet they often face challenges in efficiently managing accounting processes. The mismatch between human resource capacity and the needs of modern accounting systems is a significant issue hindering SME performance. Therefore, the development of an easy-to-use accounting information system tailored to the needs of SMEs is essential. This study aims to design and implement a digital-based accounting information system that can improve financial management efficiency in SMEs. The methods used include needs analysis, system design using the Agile methodology, and trials in several SMEs within specific regions. The results indicate that the developed system enhances the accuracy of financial record-keeping and simplifies the reporting process. Thus, this system is expected to be an effective solution for increasing the competitiveness of SMEs in the digital era.